0202 Student aspih (SASPIH): A social media strategy to drive recruitment and retention. (2nd November 2015) - Gopal, Alan; Shaw, Sebastian; Pendleton, Matthew; Taylor, Kathryn; Buttery, Blythe; Eccles, Sarah
Abstract : Background: The Association for Simulated Practice in Healthcare (ASPiH) 1 has recently created a special interest group for students – sASPiH. 2 sASPiH aims to recruit, retain and develop undergraduate healthcare professionals within ASPiH. Our business platform model 3 has been implemented, and focuses on development. Our next phase is recruitment. The dominance of social media marks it as an essential part of sASPiH's future plans. Social media overcomes geographical distance and time constraints, allowing online communities to be generated quickly and asynchronously. 4 It provides an excellent, economical method of student engagement and recruitment; however, doing so effectively requires substantial planning. Engagement requires connexion, interaction, satisfaction, retention, loyalty and advocacy; 5 without all, attrition and apathy of the user base may occur. Methodology: Our strategy was designed using existing literature and committee consensus – we aim to recruit and retain students to sASPiH by ensuring the investment of their attention is rewarded. We intend to utilise various social media outputs – Twitter, Facebook, Google+, and LinkedIn – to engage with stakeholders. Our target populations include undergraduates; trainees; senior simulation specialists; and commercial companies with the intention to build a network of simulation contacts. Our primary focus will be supporting students by providing online resources or highlighting opportunities of professional value – both internal and external to sASPiH. Anticipated outcomes: By making use of the variety of social media platforms, we hope to encourage users to increase their engagement with sASPiH. We have commenced implementation of our protocol and intend to present our performance metrics at the conference. Potential impact: Our strategy is designed to achieve two core aims. Firstly, to recruit students to sASPiH. Secondly, to develop their interests and abilities 6 and to advocate on behalf of undergraduates – allowing sASPiH to contribute to ASPiH in a transparent, accountable way. 7 References: ASPiH. About Us. ASPiH; 2014 [cited 2014 Sept 1]. Available: http://www.aspih.org.uk/about-us/ Gopal AA, Pendleton M, Cox DR. BMJ STEL. 2014;1 (Suppl1):A82–A83 Gawer A, Cusumano MA. Platform leadership. 2nd edn. Boston, MA: Harvard Business School Press, 2002 Farina-Henry E, Waterston LB, Blaisdell LL. JMIR Res Protocol 2015;4(3):e90 Sashi CM. Manag Decis. 2012;50(2):253–272 Rasmussen EA, Sorheim R. Technovation, 2006;26(2):185–194 Chesborough H. Strategy Leadersh 2007;35(6):12–17